2013
DOI: 10.1371/journal.pgen.1003549
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Desert Mammary Carcinoma Susceptibility Locus Mcs1a Regulates Nr2f1 Modifying Mammary Epithelial Cell Differentiation and Proliferation

Abstract: Genome-wide association studies have revealed that many low-penetrance breast cancer susceptibility loci are located in non-protein coding genomic regions; however, few have been characterized. In a comparative genetics approach to model such loci in a rat breast cancer model, we previously identified the mammary carcinoma susceptibility locus Mcs1a. We now localize Mcs1a to a critical interval (277 Kb) within a gene desert. Mcs1a reduces mammary carcinoma multiplicity by 50% and acts in a mammary cell-autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…These data indicate that the two observed TCE chromatin interactions are functionally distinct, and demonstrates a strong positive regulatory relationship between the Mcs5c TCE and Pappa expression, which appears to be dependent on TCE/P4-1 chromatin looping. The Mcs5c TCE/ Pappa P4-1 interaction, therefore, represents another example of a long-distance acting regulatory region, akin to those identified for the Shh [ 28 ] and Sox9 [ 29 ] genes, as well as the previously characterized Mcs1a locus [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the two observed TCE chromatin interactions are functionally distinct, and demonstrates a strong positive regulatory relationship between the Mcs5c TCE and Pappa expression, which appears to be dependent on TCE/P4-1 chromatin looping. The Mcs5c TCE/ Pappa P4-1 interaction, therefore, represents another example of a long-distance acting regulatory region, akin to those identified for the Shh [ 28 ] and Sox9 [ 29 ] genes, as well as the previously characterized Mcs1a locus [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcript quantities were calculated as described in Smits et al . [ 30 ], using a standard curve method to calculate C t values and extrapolate quantity values. Sample measurements are an average of 3–4 technical replicates and data were analyzed using SDS software version 2.2.2 (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Could some of these gains induce DTC dormancy? NR2F1 , a gene that is induced in dormancy models, and that is known to induce quiescence and lineage commitment, is located in the 5q region and was independently found to be linked to a locus that limits progression in breast cancer 134 . Perhaps DTCs overexpressing NR2F1 may remain dormant until additional genetic and/or epigenetic changes override this signal.…”
Section: Future Directionsmentioning
confidence: 99%
“…In rats, extensive genetic mapping experiments have been conducted to determine the QTLs and individual genes that control the sensitivity of the mammary gland to E 2 . Loci have been identified that regulate mammary cell proliferation and differentiation (29), mammary immune function (30), and susceptibility to E 2 ‐induced mammary cancer (31, 32). Some of these QTLs have been shown to have relevance in humans, making them interesting targets for prediction and prevention of human mammary disease (29, 33).…”
Section: Mammary Glandmentioning
confidence: 99%